Representation of violence value in Joker Film - Rosita, Eva; Prathisara, Gibbran (Universitas Ahmad Dahlan, 2022)
The Joker film aired in Indonesia on October 2, 2019. This film was widely discussed by the audience and succeeded in bringing the audience into the atmosphere of the film. This is because the problems that are taken often occur in the life of the general public. This film tells the story of Arthur aka Joker, whose life is filled with sadness, cheating, injustice as a lower middle-class citizen so that he is treated inappropriately by society and his family. Everything that happened to him resulted in the victim becoming the perpetrator of violence. Researchers are interested in analyzing the Joker film more deeply, and this is because the shows in the film contain violence that can trigger various physical and mental conditions such as aggressive behaviour, violent behaviour, bullying, fear, depression and nightmares for those who watch it. The purpose of this research is to find out how the representation of violence in the Joker film viewed from the Semiotics of Roland Barths to determine a meaning using the concepts of denotation, connotation, and myths taken from several scenes that represent the value of violence in the Joker film. The findings from the results of this study indicate that there are 16 scenes that present violence. The violence is in the form of physical violence, psychological violence, financial violence, functional violence, and rational violence. The Joker film shows that perpetrators of violence still often occur in life, even victims can become perpetrators of what happened to them. Often times people think this is normal because not everyone understands the importance of humanity and justice for others.